Seisoenale patrone in die Suid-Afrikaanse kapitaalmark - F. S. Hattingh; E. V.D.M. Smit (South African Journal of Business Management, 1993)
– Seasonal patterns in the South African capital market In this article the seasonal patterns in daily price movements of the Post Office, Eskom 168 and the RSA bonds are examined and these are compared with three equity indices namely the Gold Index, Industrial Index and Overall Index of the Johannesburg Stock Exchange. Both the South African bond and share markets display significant seasonal patterns. In contrast with international findings, it is shown that seasonal similarities exist between the bond and share markets.
Keywords: 650